RETRACTED: Early Childhood Education Learning Model in Malaysia - Sitorus, Ahmad Syukri; Muhammad, Arifin; Jelita, Dea Putri; Aulia, Putri; Sayfriani, Angela; Zainuddin, Sahida Binti (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Obsesi to article entitled "Early Childhood Education Learning Model in Malaysia"Â published in Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini Vol. 8, No. 6, has been withdrawn at the request of the author. This withdrawal was made after careful consideration by the author for specific reasons that have been communicated to the editorial board. As a result, the article has been removed from the journal archives, and any references to this article should no longer be used.This wording ensures a neutral and professional tone, avoiding any mention of violations or misconduct.Â